Fungos ectomicorrízicos do sul do Brasil, com ênfase no hábito hipógeo - Sulzbacher, Marcelo Aloisio (2010)
Fungi represent an extremely important group of organisms in terrestrial ecosystems. Among their several important ecological roles, is the mutualistic association with plant roots, forming different types of mycorrhiza. Most studies carried out so far focused on epigeous ectomycorrhizal fungi, which occur above ground. On the other hand, below ground, hypogeous ectomycorrhizal fungi, are still poorly studied. This research aimed to study the diversity of hypogeous ectomycorrhizal fungi (Basidiomycetes) collected in Eucalyptus spp. plantations in the Central Region of Rio Grande do Sul, Brazil, based on morphological and molecular characters. Samples were taken between May 2009 and July 2010. A total of five species belonging to three families were identified. The material was analyzed to determine the morphological and molecular characters. Among the species identified are: Chondrogaster pachysporus Maire, Descomyces albus (Berk.) Bougher & Castellano, Hysterangium affine Massee & Rodway in Massee, Hysterangium inflatum Rodway and Setchelliogaster tenuipes (Setch.) Pouzar. Additionally a second species of Chondrogaster sp. was collected. However, no identity was determined for this species. Furthermore, it is believed it represents a new undescribed species to science. Among the species studied, Descomyces albus is reported for the first time in the State of Rio Grande do Sul. Hysterangium affine and H. inflatum are newly recorded species from Brazil while Chondrogaster pachysporus is recorded for the first in South America.